My life with Charlie Brown - Schulz, Charles M. (Charles Monroe), 1922-2000 (University Press of Mississippi, 2010)
While best known as the creator of Peanuts, Charles M. Schulz (1922-2000) was also a thoughtful and precise prose writer who knew how to explain his craft in clear and engaging ways. My Life with Charlie Brown brings together his major prose writings, many published here for the first time. Schulz's autobiographical articles, book introductions, magazine pieces, lectures, and commentary elucidate his life and his art, and clarify themes of modern life, philosophy, and religion that are interwoven into his beloved, groundbreaking comic strip. Edited and with an introduction by comics scholar M.